Overview of Effect of Game Means on Dynamics of Strength Development in Junior Girls - Т. Ю. Нікітенкова; С. І. Марченко (OVS LLC, 2017)
The research objective is to analyze the effect of game means on the dynamics of strength development in the second-, third- and fourth-grade girls. Materials and methods: the participants in the study were 104 schoolgirls: 32 - second-graders, 32 - third-graders, and 40 - fourth-graders. To achieve the tasks set, the research used the following methods: theoretical analysis and summary of scientific and methodological literature, method of control testing, pedagogical experiment, methods of mathematical statistics. Results: the results of the analysis of variance in correlating the data indicate to what degree various game modes influence the development of strength abilities in the second-, third- and fourth-grade girls. The study observed the strongest effect of the factor in the second-grade girls in the second group - 88.7%, fourth group - 90%, sixth group - 85.4%, and eighth group - 76.4%. The third-grade girls demonstrated the strongest effect of the factor in the eighth group - 82.7%. The fourth-grade girls showed the strongest effect of the motion mode in the sixth group - 74.8% and in the eighth group - 69.7%. Conclusions: It is advisory to use small loads and bodyweight exercises when developing strength abilities in junior girls. Games are performed at a quick and moderate pace. Games should be diverse to involve different muscle groups. The number of games can vary from four to eight depending on the level of physical development and physical preparedness of the schoolers.